Creative Accounting: Techniques of Application-An Empirical Study among Auditors and Accountants of Listed Companies in Bangladesh - Asif, Mahbub Karim; Junaid, M. Shaikh; Hock, Oo Yu; Md. Rafiqul, Islam (2016)
Creative Accounting, also known as Hollywood accounting, income smoothing, cosmetic accounting is a legitimate accounting application where by the accountants and auditors take advantage of the loopholes in the accounting policies as per International Accounting Standards (IAS) and Generally Accepted Accounting Principles (GAAP). It is not a fraudulent practice, as the concerned parties involved here only take the advantage of the accounting policy loopholes to better represent financial statements. This research is conducted on the empirical data collected from the auditors and the accountants of the listed companies of Bangladesh to determine the popularity of Creative Accounting application among accountants and auditors in Bangladesh. The paper discusses the various findings from the research which shows that at least some evidence of expense assetization and that there is any gap in the perception between the auditors and accountants regarding techniques and methods of creative accounting. The technique may be used to increase or decrease income in order to show higher or lower profit, to turn expenses into assets so as to increase profitability or to maneuver the net worth of the business.